2011
DOI: 10.1002/qj.955
|View full text |Cite
|
Sign up to set email alerts
|

A new floating model level scheme for the assimilation of boundary‐layer top inversions: the univariate assimilation of temperature

Abstract: The assimilation of observations with a forecast is often heavily influenced by the description of the error covariances associated with the forecast. When a temperature inversion is present at the top of the boundary layer (BL), a significant part of the forecast error may be described as a vertical positional error (as opposed to amplitude error normally dealt with in data assimilation). In these cases, failing to account for positional error explicitly is shown to result in an analysis for which the inversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…When the assimilation of observations attempts to correct this positional error, instead of shifting the profiles, it erroneously changes the structure of the temperature and salinity profiles so that the error in the analysis is actually increased compared to the background. This is an issue for all three coupling strategies and is a well-documented problem in the atmosphere when assimilating observations of the analogous boundary layer capping inversion (Fowler et al, 2012).…”
Section: Assimilation Resultsmentioning
confidence: 99%
“…When the assimilation of observations attempts to correct this positional error, instead of shifting the profiles, it erroneously changes the structure of the temperature and salinity profiles so that the error in the analysis is actually increased compared to the background. This is an issue for all three coupling strategies and is a well-documented problem in the atmosphere when assimilating observations of the analogous boundary layer capping inversion (Fowler et al, 2012).…”
Section: Assimilation Resultsmentioning
confidence: 99%
“…This method could be used to displace features in 3D, but Nehrkorn et al (2014) and other studies have applied this to displace fields only horizontally. Fowler et al (2012) on the other hand used a grid distortion method to shift the BL inversion vertically. In this scheme, a new parameter, a, is analysed (together with the usual amplitude adjustments), where a specifies how the usual model level heights (z i ) should be shifted to new heights (z i ):z i = z i + aD(z i ).…”
Section: Sharp Features and Their Position Errorsmentioning
confidence: 99%
“…For operational meteorology, modern radiosondes sample the atmosphere every second during ascent (World Meteorological Organization, 2014), which can take up to 2 hr. Typically, radiosondes are launched from fixed sites that are widely separated (approximately 100 km) and report at fixed times (usually 0000 and 1200 UTC) and so do not provide sufficient horizontal spatial or temporal resolution to capture the onset or duration of a temperature inversion (Fowler, 2010).…”
Section: In Situ Upper Air Temperature Observationsmentioning
confidence: 99%
“…An elevated inversion in effect caps vertical movement and dispersion of atmospheric aerosols. This may affect the forecast conditions for solar insolation and the formation or persistence of fog and cloud (Fowler et al, ). It is suggested that T MACH observations could provide an additional source of information, albeit a qualitative source, on the vertical temperature profile that may otherwise be unknown, since the 0600 Herstmonceux radiosonde report is made only on demand (unlike the reports at 0000 and 1200).…”
Section: Inversion Case Studymentioning
confidence: 99%
See 1 more Smart Citation